Arahan Penataan Permukiman Pulau Kecil Berbasis Mitigasi Abrasi di Pulau Lamputang, Kabupaten Pangkep - Novita Kumala Putri; Mimi Arifin; Mukti Ali (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2020)
Lamputang Island is one of the small islands in Pangkep Regency, with a total population of 439 people. Based on statistics, this island has changed its shape and area every year, since 2013-2018 this island has changed an area of 1.1 hectares. This study aims to determine the level of the threat of abrasion based on physical characteristics on Lamputang Island, the level of vulnerability of the abrasion area based on settlement patterns on Lamputang Island and the direction of settlement arrangement based on abrasion mitigation on Lamputang Island. This research was conducted from June 2019 to February 2020. This research is located on Lamputang Island, Pangkep Regency. Data collection techniques are observation, interviews, questionnaires, and literature studies. The analytical method used is descriptive qualitative methods, quantitative threats and vulnerabilities and spatial. The results showed that Lamputang Island was at a moderate level of threat and high vulnerability, with a random settlement pattern. The direction for settlement arrangement on this island is in the form of zoning for areas prone to abrasion, settlement mitigation, and arrangement of settlement patterns.